ANALISIS PRODUKTIVITAS PERBANKAN SYARIAH DI INDONESIA BERDASARKAN MALMQUIST PRODUCTIVITY INDEX - Apik Nurfikasari, Heraeni Tanuatmodjo Suci Apriliani Utami (UIN Mataram, 2019)
Syariah Commercial Banks in Indonesia have not been able to increase their productivity in managing financial funds entirely due to the inability to respond technological changes. This is what makes Syariah Banks in Indonesia still unable to compete with conventional banks. The purpose of this study was to determine the picture of Syariah banking productivity based on the Malmquist Productivity Index. This research is a quantitative study using descriptive analysis. The data used in this research are secondary datas. The population of this study is Islamic commercial banks in Indonesia in the 2014-2018 period, with a sample of 12 banks. Sampling is done by using purposive sampling method. The results showed that BNI Syariah Bank was the most productive Islamic bank during the 2014-2018 period and of the 12 Islamic banks studied and only BCA Syariah experienced a decrease in productivity in the 2014-2018 period.